Coronavirus (COVID-19): How to Secure the Supply Chain? – A Case Study - Rubén Medina Serrano; Reyes Gonzalez; Jose Gasco; Wanja Wellbrock (International Journal of Supply Chain Management, 2020)
Supply chain global dependency has been arisen in the last years and supply chain managers want to know if the manufacturing purchasing managers’ index and export/import dependency rate data are effective qualitative key performance indicators (KPIs) to monitor possible supply chain risk effects in a proper way. The aim of this study is to address this question performing an analysis of the current KPIs in the main affected countries in Europe (Italy) and Asia (China). After a review of the literature on Supply Chain Risk Management (SCRM) and published official statistics in China, Italy and Germany, a case study focused on a set of interviews with practitioners based on a firm located in Germany was used to generate uncaptured insights in previous research of the area. Official KPIs and firms’ supplier specific KPIs like delivery performance are key to monitor possible Supply chain disruptions. Moreover, increasing regular bidirectional communication with firms’ suppliers generates trust and it is one of the most critical issues which can positively influence on firm’s performance. A regular follow-up of authorities’ updates in terms of restrictions at local, national and international level should be considered too. This paper identifies manufacturing purchasing managers’ index and export/import dependency rate data as effective qualitative KPIs to monitor possible supply chain risk effects and disruptions in a structured manner and to outline future research opportunities in the field of SCRM.